Mentalization-based treatment for personality disorders: efficacy, effectiveness, and new developments - Volkert, Jana; Hauschild, Sophie; Taubner, Svenja (Current psychiatry reports, 2019)
Purpose of the ReviewThis review aims to outline the most recent evidence on the efficacy and effectiveness of mentalization-based treatment (MBT) for personality disorders (PD) from 2015 to 2018 and to describe new treatment developments.Recent FindingsSince 2015, 14 new—primarily effectiveness—MBT trials have been published. The main body of studies investigated adult populations (n = 11), patients with a borderline personality disorder (BPD) diagnosis (n = 8), and compared MBT with another psychotherapeutic treatment (n = 6). The majority of studies suggest that MBT has the potential to improve the clinical outcomes for adolescents and adults with a PD diagnosis, particularly BPD, and also with comorbid diagnoses and there are indications for changes in mentalizing being a specific mechanism of change promoted by MBT.SummaryDespite promising findings, there is an urgent need for methodological sound and sufficiently powered studies to investigate both the efficacy and effectiveness of MBT, especially beyond BPD.
Gesehen am 03.04.2019